Antioxidant for fuel cell and fuel cell including the antioxidant

Through the cerium reduction reaction annealing treatment and multiple annealing processes, the microstructure of the cerium-based oxide is controlled, which solves the problem that the antioxidant capacity and stability of the cerium oxide are inversely proportional, and realizes the efficient antioxidant and acid resistance of the antioxidant in the fuel cell. sex.

CN111755727BActive Publication Date: 2025-01-24HYUNDAI MOTOR CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202010095727.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-02-17
Publication Date
2025-01-24
Estimated Expiration
2040-02-17

AI Technical Summary

Technical Problem

In the prior art, the antioxidant ability of cerium oxide is inversely proportional to the long-term stability, and it is difficult to ensure excellent antioxidant ability and acid resistance at the same time.

Method used

The crystal structure of the cerium-based oxide is precisely controlled through cerium reduction reaction annealing treatment, a compound including samarium and cerium oxide is prepared, and primary annealing and secondary annealing are performed to obtain an antioxidant.

Benefits of technology

Significantly improves the antioxidant capacity and acid resistance of antioxidants, ensuring the long-term stability and efficient performance of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111755727B_ABST
    Figure CN111755727B_ABST
Patent Text Reader

Abstract

The present application discloses an antioxidant for increasing the chemical durability of a polymer electrolyte membrane fuel cell (PEMFC) and a method for manufacturing the same. The antioxidant can prevent the chemical degradation of the fuel cell through a reduction reaction annealing treatment and has an improved antioxidant capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an antioxidant for a fuel cell having improved antioxidant capacity. Background Art

[0002] Polymer electrolyte membrane fuel cells (PEMFCs) for vehicles are power generation devices that generate electricity through electrochemical reactions between hydrogen and oxygen in the air, and are well known as next-generation environmentally friendly energy sources that have high power generation efficiency and do not emit effluents other than water. Moreover, polymer electrolyte membrane fuel cells can generally operate at temperatures of 95°C or lower and achieve high power density.

[0003] This reaction of generating electricity in a fuel cell occurs in a membrane electrode assembly (MEA) including a perfluorinatedsulfonic acid ionomer-based electrolyte membrane, an anode, and a cathode. Hydrogen supplied to the oxidation electrode, i.e., the anode, of the fuel cell is separated into protons and electrons. The protons move to the reduction electrode, i.e., the cathode, through the membrane, and the electrons move to the cathode through an external circuit. Oxygen molecules, protons, and electrons react together at the cathode, thereby generating electricity and heat, while generating water (H2O) as a byproduct. 2 O).

[0004] Typically, the reactant gases of a fuel cell, i.e., hydrogen and oxygen in the air, pass through the electrolyte membrane, thereby promoting the generation of hydrogen peroxide (HOOH), which generates oxygen-containing free radicals, such as hydroxyl radicals (·OH), hydroperoxyl radicals (·OOH), etc. These free radicals attack the electrolyte membrane based on perfluorosulfonic acid ionomer, thereby causing chemical degradation of the membrane, which ultimately has adverse effects, such as reducing the durability of the fuel cell.

[0005] As a conventional technique for alleviating such chemical degradation of the electrolyte membrane, methods of adding various antioxidants to the electrolyte membrane have been proposed.

[0006] For example, antioxidants are divided into a first antioxidant acting as a free radical scavenger and a second antioxidant acting as a hydrogen peroxide decomposition agent. The first antioxidant includes a cerium-based antioxidant, such as cerium oxide, cerium (III) nitrate hexahydrate, terephthalate-based antioxidants, etc. The second antioxidant includes a manganese-based antioxidant, such as manganese oxide, etc.

[0007] However, in the prior art, cerium oxide is generally known to have a problem that its antioxidant ability and long-term stability are inversely proportional to each other.

[0008] Therefore, in order to simultaneously ensure excellent antioxidant capacity and acid resistance, the microstructural properties of cerium-based oxides need to be optimally controlled.

[0009] The above information disclosed in this Background section is only for enhancement of understanding of the background of the invention and therefore it may contain information that does not form the prior art that is already known to a person of ordinary skill in the art in this country. Summary of the invention

[0010] In a preferred aspect, the crystal structure of the cerium-based oxide is precisely controlled by a cerium reduction reaction annealing treatment, thereby providing a method for producing an antioxidant having greatly improved antioxidant capacity.

[0011] In one aspect, a method for manufacturing an antioxidant for a fuel cell is provided, the method comprising the steps of: preparing a compound including samarium and cerium oxide; performing a primary annealing on the compound; and performing a secondary annealing on the resultant obtained by the primary annealing to obtain the antioxidant. Specifically, the secondary annealing can be performed at a temperature equal to or lower than the primary annealing temperature.

[0012] As used herein, the term "cerium oxide" refers to a substance composed of cerium and oxygen (e.g., composed of cerium ions (cations, such as Ce 4+ or Ce 3+ ) and oxide anions (O -2 Preferably, the cerium oxide may be a compound having the formula CeO 2 The cerium oxide can form a stable crystal structure (for example, a cubic or fluorite structure).

[0013] The compound may suitably be samarium (Sm)-doped cerium oxide.

[0014] As used herein, the term "samarium (Sm)-doped cerium oxide" refers to a cerium oxide that is doped with one or more cerium ions (e.g., Ce) in the crystal structure of the compound. 4+ or Ce 3+ ) with one or more samarium ions (e.g. Sm 2+ or Sm 3+ ) is replaced by a cerium oxide compound modified or doped. For example, when Ce in a crystal unit is replaced by 4+ Use Sm 3+ During the substitution, a free electron is released in the unit, which results in an increase in the electrical conductivity of the compound's crystal structure (eg, fluorite structure).

[0015] Samarium-doped cerium oxide can be represented by Chemical Formula 1,

[0016] [Chemical formula 1]

[0017] Smx Ce 1-x O 2-δ ,

[0018] Here, 0 < x ≤ 0.5, and it can represent the oxygen vacancy value that makes the samarium-doped cerium oxide shown in Chemical Formula 1 electrically neutral.

[0019] The first annealing can be carried out at a temperature of about 100 °C to 1,000 °C, and the second annealing can be carried out at a temperature equal to or lower than the temperature of the first annealing. For example, the second annealing can be carried out at a temperature equal to the temperature of the first annealing or about 5, 10, 15, 20, 25, 30, 40, 50 °C or more lower than the temperature of the first annealing.

[0020] The first annealing and the second annealing can be carried out for about 10 minutes to 10 hours respectively.

[0021] The first annealing can be carried out in an ambient atmosphere, and the second annealing can be carried out in a gas atmosphere including hydrogen.

[0022] Compared with the product formed by the first annealing, the antioxidant obtained by the second annealing can have a greater Raman peak intensity at 553 cm -1 and 600 cm -1 .

[0023] On the other hand, a fuel cell is provided, which includes: a membrane electrode assembly including an electrolyte membrane and a pair of electrodes formed on two surfaces of the electrolyte membrane; a gas diffusion layer; and a separator. Specifically, at least one of the electrolyte membrane, the electrodes, and the gas diffusion layer includes the antioxidant described herein.

[0024] The antioxidant can appropriately have main diffraction peaks in the regions of 2θ = 28 ± 1.0 °, 32 ± 1.0 °, 47 ± 1.0 °, and 56 ± 1.0 ° in the XRD spectrum.

[0025] The antioxidant can appropriately have a crystallite size of about 5 nm to 50 nm and a BET specific surface area of about 10 m 2 / g to 200 m 2 / g.

[0026] The electrolyte membrane can include about 100 ppm to 100,000 ppm of the antioxidant.

[0027] A vehicle is also provided, which can include the fuel cell described herein.

[0028] Other aspects and preferred embodiments of the present invention are discussed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The above and other features of the present invention will now be described in detail with reference to certain exemplary embodiments thereof illustrated in the accompanying drawings, which are given hereinafter for illustration only and therefore do not constitute a limitation of the present invention, in which:

[0030] Figure 1 is a cross-sectional view briefly illustrating an exemplary membrane electrode assembly according to an exemplary embodiment of the present invention;

[0031] Figure 2 is a cross-sectional view illustrating an exemplary electrolyte membrane according to an exemplary embodiment of the present invention;

[0032] Figure 3 is a cross-sectional view illustrating an exemplary electrolyte membrane according to an exemplary embodiment of the present invention;

[0033] Figure 4 is a flow chart illustrating an exemplary method of making an exemplary antioxidant according to an exemplary embodiment of the present invention;

[0034] Figure 5 is a graph showing the results of X-ray diffraction analysis of antioxidants according to Examples and Comparative Examples;

[0035] Figure 6 are photographs showing the results of measuring the antioxidant abilities of the antioxidants according to Examples and Comparative Examples by a technique using methyl violet;

[0036] Fig. 7A is a graph showing the results of measuring the antioxidant abilities of the antioxidants according to Comparative Example A, Example A-1, and Example A-2 by UV-visible spectroscopy;

[0037] Figure 7B is a graph showing the results of measuring the antioxidant abilities of the antioxidants according to Comparative Example B, Example B-1, and Example B-2 by UV-visible spectroscopy;

[0038] Fig. 8A is a graph showing the results of measuring changes in oxygen vacancy concentrations of antioxidants according to Comparative Example A, Example A-1, and Example A-2 by Raman spectroscopy;

[0039] Figure 8B is a graph showing the results of measuring changes in oxygen vacancy concentrations of the antioxidants according to Comparative Example B, Example B-1, and Example B-2 by Raman spectroscopy; and

[0040] Fig. 9 It is a graph showing the measurement results of the acid resistance of the antioxidants according to Comparative Example B, Example B-1, and Example B-2.

[0041] It should be understood that the drawings are not necessarily to scale, but rather are slightly simplified representations of various preferred features illustrating the basic principles of the invention. The specific design features of the present invention disclosed herein, including, for example, specific size, orientation, location and shape, will be determined in part by the specific intended application and use environment.

[0042] In the drawings, reference numbers refer to the same or equivalent parts of the present invention throughout the several figures. DETAILED DESCRIPTION

[0043] Reference will be made in detail to various embodiments of the invention, examples of which are illustrated in the accompanying drawings and described below. Although the invention will be described in conjunction with the exemplary embodiments, it should be understood that this description is not intended to limit the invention to the exemplary embodiments. On the contrary, the invention is intended to cover not only the exemplary embodiments, but also various variations, modifications, equivalents and other embodiments, all of which are within the spirit and scope of the invention as defined in the claims.

[0044] In the following description of the embodiments, terms such as "including", "having", etc. should be understood to indicate the existence of the described features, numbers, steps, operations, elements or components, or a combination thereof, and do not exclude the existence of one or more other features, numbers, steps, operations, elements, components or a combination thereof, or the possibility of adding them.

[0045] Furthermore, it should be understood that when a part such as a layer, film, region or plate is referred to as being "on" another part, the part may be "directly" located on the other part, or other parts may be interposed between the two parts. Similarly, it should be understood that when a part such as a layer, film, region or plate is referred to as being "under" another part, the part may be "directly" located under the other part, or other parts may be interposed between the two parts.

[0046] All numbers, values ​​and / or expressions used in this specification that represent the amount of components, reaction conditions, polymer compositions and mixtures are approximate values ​​that reflect the various measurement uncertainties that arise when these values ​​are obtained from essentially different things. Therefore, unless otherwise indicated, it is understood that they are all modified by the term "about". Moreover, unless specifically stated or clearly derived from the context, the term "about" used herein should be understood to be within the normal tolerance range in this field, such as within 2 standard deviations of the mean. "About" can be understood to be within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05% or 0.01% of the value. Unless otherwise clearly derived from the context, all numerical values ​​provided herein are modified by the term "about".

[0047] In addition, it should be understood that when numerical ranges are disclosed in the specification, unless otherwise indicated, these ranges include all continuous values ​​from the minimum value to the maximum value. Moreover, when such ranges are integers, unless otherwise indicated, the ranges include all integers from the minimum integer to the maximum integer.

[0048] It should be understood that the term "vehicle" or "vehicular" or other similar terms used herein include conventional motor vehicles, such as passenger cars including sport utility vehicles (SUVs), buses, trucks, various commercial vehicles, watercraft including various boats and ships, aircraft, etc., and include hybrid vehicles, electric vehicles, plug-in hybrid electric vehicles, hydrogen-powered vehicles, and other alternative fuel vehicles (e.g., fuels derived from resources other than petroleum). As referred to herein, a hybrid vehicle is a vehicle having two or more power sources, for example, a vehicle having both gasoline power and electric power.

[0049] Hereinafter, a detailed description will be given of an exemplary antioxidant and an exemplary membrane electrode assembly according to various exemplary embodiments of the present invention with reference to the accompanying drawings.

[0050] Figure 1 1 is a cross-sectional view briefly illustrating a membrane electrode assembly 1 according to the present invention. Figure 1 As shown, the membrane electrode assembly 1 includes an electrolyte membrane 10 and a pair of electrodes formed on both surfaces of the electrolyte membrane 10. Here, the pair of electrodes refers to an anode and a cathode, and the anode and the cathode are positioned opposite to each other with the electrolyte membrane 10 interposed therebetween.

[0051] The fuel cell according to the present invention includes a membrane electrode assembly 1, a gas diffusion layer and a separator.

[0052] At least one of the electrolyte membrane 10 and the pair of electrodes 20 includes an antioxidant.

[0053] Figure 2 is a cross-sectional view illustrating an exemplary electrolyte membrane 10. Figure 2 In the embodiment, the electrolyte membrane 10 may be a single membrane structure including a mixture 11 of a perfluorosulfonic acid ionomer and an antioxidant.

[0054] Figure 3 is a cross-sectional view illustrating another exemplary electrolyte membrane 10. Figure 3 In the embodiment, the electrolyte membrane 10 may have a three-layer structure formed by impregnating a reinforcing layer 12 to increase the mechanical rigidity of the electrolyte membrane 10 with a mixture 11 of a perfluorosulfonic acid ionomer and an antioxidant.

[0055] The reinforcement membrane 12 may be formed of expanded polytetrafluoroethylene (e-PTFE), and is a porous membrane having many pores.

[0056] However, the electrolyte membrane 10 according to the present invention is not limited to Figure 2 and Figure 3 types, and is understood to have any type including perfluorosulfonic acid ionomer (for conducting ions) and an antioxidant.

[0057] The electrolyte membrane 10 may include an antioxidant in an amount of about 100 ppm to 100,000 ppm based on the content of the perfluorosulfonic acid ionomer. When the content of the antioxidant is less than about 100 ppm, the antioxidant ability of the electrolyte membrane 10 is excessively reduced, so the improvement of the chemical durability of the electrolyte membrane 10 is not significant. On the contrary, when the content of the antioxidant is greater than about 100,000 ppm, the proton conductivity of the electrolyte membrane 10 is greatly reduced and the brittleness of the electrolyte membrane 10 increases.

[0058] The perfluorosulfonic acid ionomer may suitably include Nafion. Preferably, the perfluorosulfonic acid ionomer may be Nafion.

[0059] The antioxidant may include: a compound including samarium (Sm) and cerium oxide. Preferably, the antioxidant may be samarium (Sm)-doped cerium oxide that can be formed or prepared by annealing.

[0060] Figure 4 is a flowchart illustrating a method of manufacturing an antioxidant. In Figure 4 , the method of manufacturing an antioxidant may include: preparing samarium (Sm)-doped cerium oxide (hereinafter referred to as "SDC") (operation S1); performing a first annealing on the SDC (operation S2); and performing a second annealing on the SDC that has been first annealed (operation S3).

[0061] By substituting some tetravalent cerium ions (Ce 3+ ) of cerium oxide (CeO 2 ) having a fluorite-type structure with trivalent samarium ions (Sm 4+ ), SDC can be formed, which may have increased oxygen vacancies and thus may have improved redox reaction characteristics.

[0062] SDC may be represented by the following Chemical Formula 1.

[0063] [Chemical Formula 1]

[0064] Sm x Ce 1-x O 2-δ ,

[0065] Here, 0 < x ≤ 0.5, and δ represents the oxygen vacancy value that makes the compound shown in the above Chemical Formula 1 electrically neutral.

[0066] When x is greater than 0.5, the inherent structural properties of SDC will decrease, so x can satisfy the above numerical range.

[0067] In the antioxidant according to the present invention, SDC may be a base material for the antioxidant. In the following description, "base material for the antioxidant" may refer to an original base material to which no treatment such as annealing is applied.

[0068] In the preparation of SDC (operation S1), SDC may be prepared by various methods, for example, a hydrothermal synthesis method, a flame hydrolysis deposition method, a sol-gel autocombustion method, or a combination thereof, which is not limited.

[0069] In order to simultaneously ensure excellent antioxidant ability and acid resistance of the antioxidant in the acid environment of polymer electrolyte membrane fuel cells for vehicles, it is necessary to optimally control the fine structural characteristics of SDC such as crystallite size, specific surface area, etc.

[0070] For this purpose, the present invention also provides a method for preparing an antioxidant by: performing a primary annealing on SDC under specific conditions to preferentially control the crystallite size and specific surface area of ​​SDC; and then performing a secondary annealing on the resulting product obtained by the primary annealing to ensure the excellent antioxidant capacity and acid resistance of the antioxidant.

[0071] Preferably, the secondary annealing (operation S3) may be performed at a temperature that may be equal to or lower than the temperature of the primary annealing (operation S2). The primary annealing (operation S2) may be performed at a temperature of about 100°C to 1,000°C, and the secondary annealing (operation S3) may be performed at a temperature that is equal to or lower than the temperature of the primary annealing (operation S2). In the description of the embodiments of the present invention, it should be understood that the term "equal to" includes the meanings of equal to, slightly higher than, and slightly lower than. For example, the term "equal to" should be understood to include a range of ±5, ±10, ±15, ±20, etc., which deviates from the numerical value used as a reference value.

[0072] When the primary annealing (operation S2) is performed at a temperature lower than about 100°C, the effect of annealing is not significant, so the antioxidant may have high antioxidant capacity but low acid resistance; when the primary annealing (operation S2) is performed at a temperature higher than about 1,000°C, the effect of annealing is excessive, so the antioxidant may have high acid resistance but low antioxidant capacity. Moreover, when the secondary annealing (operation S3) is performed at a temperature higher than the temperature of the primary annealing (operation S2), the crystallite size of the antioxidant is additionally increased, so the antioxidant capacity of the antioxidant is too low.

[0073] The primary annealing (operation S2) and the secondary annealing (operation S3) can be performed for 10 minutes to 10 hours, or specifically, about 30 minutes to 4 hours. When the annealing time is less than 10 minutes, the annealing effect will be insufficient, and when the annealing time is greater than about 10 hours, the process cycle time will be too increased.

[0074] The primary annealing (operation S2) may be performed in an atmospheric atmosphere, and the secondary annealing (operation S3) may be performed in a gas atmosphere including hydrogen. When the secondary annealing (operation S3) is performed in a gas atmosphere including hydrogen, the surface of the SDC may be effectively reduced, and thus the antioxidant capacity of the antioxidant may be further improved. Moreover, as the proportion of hydrogen in the gas including hydrogen increases, the time taken to reduce the SDC may be shortened, and the effect thereof may be increased.

[0075] The primary annealing (operation S2) and the secondary annealing (operation S3) may be performed continuously or intermittently.

[0076] When the primary annealing (operation S2) and the secondary annealing (operation S3) are performed continuously, the primary annealing (operation S2) of the SDC can be performed in a chamber having a specified shape and size, the internal temperature of the chamber can be maintained or reduced, and then immediately, the secondary annealing (operation S3) of the resulting product obtained by the primary annealing (operation S2) can be performed in the same chamber.

[0077] On the other hand, when the primary annealing (operation S2) and the secondary annealing (operation S3) are performed intermittently, after the primary annealing (operation S2) of the SDC is performed in a chamber maintained at a specific temperature, the resulting product obtained by the primary annealing (operation S2) can be supplied to another chamber maintained at a temperature that is the same as or lower than the temperature of the chamber in which the primary annealing (operation S2) is performed, and the secondary annealing (operation S3) of the resulting product can be performed in the chamber.

[0078] However, the annealing of the SDC is not limited to the above method, and it can be performed by any method that can achieve the object of the present invention.

[0079] Example

[0080] Hereinafter, the antioxidant according to the present invention will be described in more detail through the following examples.

[0081] Preparation of antioxidants

[0082] Antioxidants according to Examples and Comparative Examples were prepared under the conditions shown in Table 1 below.

[0083] Table 1

[0084]

[0085] The crystallite size, antioxidant ability, oxygen vacancy concentration change, and acid resistance of the antioxidants according to Examples and Comparative Examples were measured as follows.

[0086] Crystallite size

[0087] Generally, crystallite size can be measured using a variety of techniques, such as gas adsorption and X-ray diffraction (XRD), and even the same material may have widely different crystallite size values ​​depending on the measurement method. Therefore, in the present invention, the crystal structure of the antioxidant is analyzed by the more commonly used technique X-ray diffraction using an X-ray diffractometer (X'Pert Pro, manufactured by Panalytical Co. of the Netherlands), and then the crystallite size of the antioxidant is calculated using the Debye-Scherrer equation.

[0088] Figure 5 is a graph showing the results of X-ray diffraction analysis of the antioxidants according to Examples and Comparative Examples, and the following Table 2 shows the crystallite sizes of the antioxidants.

[0089] Table 2

[0090]

[0091]

[0092] like Figure 5 As shown, it can be understood that the antioxidant shows main diffraction peaks at 2θ=28±1.0°, 32±1.0°, 47±1.0° and 56±1.0° in the XRD spectrum. As shown in Table 2, whether or not the secondary annealing is performed, there is no significant difference in crystallite size between the antioxidants according to Comparative Example A, Example A-1 and Example A-2 within the limit of measurement error.

[0093] On the other hand, according to the results of Comparative Examples A and B, Examples A-1 and B-1, and Examples A-2 and B-2, it can be understood that when the primary annealing temperature is increased from 600°C to 800°C, as shown in FIG. Figure 5 As exemplified in , the characteristic peaks of the antioxidant crystallites are more clearly apparent, and thus, the crystallite size calculated using the Debye-Scherrer equation increases by about 7-8 nm on average.

[0094] In the same manner, whether or not the secondary annealing is performed, within the measurement error limit, there is no significant difference in crystallite size between the antioxidants according to Comparative Example B, Example B-1, and Example B-3. On the other hand, it can be understood that when the secondary annealing temperature is much higher than the primary annealing temperature (e.g., 100° C. or more), as shown in Comparative Examples B-1 and B-2, the crystallite size of the antioxidant increases rapidly. Therefore, in order to minimize the change in crystallite size after the primary annealing, the secondary annealing temperature may be equal to or lower than the primary annealing temperature.

[0095] Antioxidant Capacity

[0096] 1) Antioxidant capacity measured by the technique using methyl violet

[0097] The technique using methyl violet is as follows: methyl violet is reacted with iron (II) sulfate heptahydrate (FeSO 4 7H 2 O), hydrogen peroxide, deionized water, and an antioxidant are mixed; and the color change of methyl violet is observed.

[0098] When the antioxidant capacity of the antioxidant increases, the initial color of methyl violet, ie, purple, is well maintained, and when the antioxidant capacity of the antioxidant decreases, the initial color of methyl violet, ie, purple, gradually fades and eventually disappears (colorless).

[0099] In the present invention, in order to evaluate the antioxidant capacity of the antioxidants according to the examples and comparative examples, methyl violet aqueous solution, iron (II) sulfate heptahydrate (FeSO 4 7H 2 O) and hydrogen peroxide were mixed in a molar ratio of 1:40:40 to prepare a methyl violet test solution, and then about 3 mg of the antioxidant according to the embodiment and the comparative example were added to the methyl violet test solution. The test results are as follows: Figure 6 shown.

[0100] like Figure 6 As shown, it can be confirmed that the color of the methyl violet test solution to which the antioxidants according to Comparative Examples A and B were added is greatly faded compared to the color of the undiluted methyl violet aqueous solution. It can be understood that when the primary annealing temperature increases, the antioxidant capacity of the antioxidant decreases, and the color of the test solution to which the antioxidant according to Comparative Example B (in which the primary annealing temperature is relatively high) is added is lighter than the color of the test solution to which the antioxidant according to Comparative Example A is added.

[0101] According to the results of the antioxidants of Examples A-1 and A-2 and Examples B-1 and B-2, it can be understood that when the secondary annealing is performed, the retention of the purple color is enhanced. Specifically, compared with Comparative Examples A and B (in which a single primary annealing is performed), in the antioxidants according to Examples A-2 and B-2 (in which the secondary annealing is performed at a temperature of 600° C.), it is observed with the naked eye that the retention of the purple color is greatly enhanced. Therefore, it can be confirmed that the antioxidant capacity of the antioxidant is greatly improved by performing the secondary annealing.

[0102] 2) Antioxidant capacity measured by UV-visible spectroscopy

[0103] The antioxidant capacity of the antioxidants according to the examples and comparative examples was evaluated more accurately by comparatively measuring the absorption intensity of the methyl violet test solution to which the antioxidants according to the examples and comparative examples were added using a UV-visible spectrophotometer (UV-3600, Shimadzu Corporation, Japan). The measurement results are shown in Fig. 7A and 7B . Fig. 7A is a graph showing the results of measuring the antioxidant capacity of the antioxidants according to Comparative Example A, Example A-1 and Example A-2, Figure 7B It is a graph showing the measurement results of the antioxidant abilities of the antioxidants according to Comparative Example B, Example B-1, and Example B-2.

[0104] Therefore, when the antioxidant ability of the antioxidant is high, the antioxidant has a high absorption intensity at a wavelength of about 580 nm (ie, the intrinsic absorption wavelength of methyl violet), and when the antioxidant ability of the antioxidant is low, the antioxidant has a low absorption intensity at a wavelength of about 580 nm.

[0105] like Fig. 7A As shown, it can be confirmed that, compared with the UV-visible absorption intensity of the antioxidant according to Comparative Example A, the UV-visible absorption intensity of the antioxidants according to Examples A-1 and A-2 increases in sequence.

[0106] like Figure 7B As shown, it can be confirmed that, compared with the UV-visible absorption intensity of the antioxidant according to Comparative Example B, the UV-visible absorption intensity of the antioxidants according to Examples B-1 and B-2 increases in sequence.

[0107] Therefore, it can be understood that the antioxidant ability of the antioxidant is improved by performing the secondary annealing.

[0108] Specifically, it can be confirmed that the UV-visible absorption intensity of the antioxidant according to Example B-2 (in which the primary annealing was performed at a temperature of 800° C. and the secondary annealing was performed at a temperature of 600° C.) is greatly increased compared with the UV-visible absorption intensity of the antioxidant according to Comparative Example B.

[0109] Changes in oxygen vacancy concentration

[0110] In order to verify the change in oxygen vacancy concentration of the antioxidants according to the examples and comparative examples, analysis was performed by Raman spectroscopy. The analysis results are shown in Fig. 8A and 8B middle. Fig. 8A is a graph showing the analysis results of the antioxidants according to Comparative Example A, Example A-1 and Example A-2, Figure 8B It is a graph showing the analysis results of the antioxidants according to Comparative Example B, Example B-1 and Example B-2.

[0111] according to Fig. 8A and 8B As shown in the results, it can be understood that when the secondary annealing is performed, the characteristic peak of the antioxidant in the change of oxygen vacancy concentration (i.e., 553 cm -1 and 600cm -1 ) gradually increases. Therefore, it can be determined that the improvement of the antioxidant ability of the antioxidant by secondary annealing in the present invention is caused by the increase in the concentration of oxygen vacancies present in the crystal structure of the antioxidant.

[0112] Acid resistance

[0113] In order to compare the acid resistance of the antioxidants according to Examples B-1 and B-2 and Comparative Example B, an acid resistance test was performed in an acid environment simulating the actual working conditions of a polymer electrolyte membrane fuel cell. The antioxidants were respectively saturated with 2M sulfuric acid (H 2 SO 4 ) solution for 48 hours, and then the absorption intensity of the solution in which the antioxidant was impregnated was measured using a UV-visible spectrophotometer to detect the acid resistance of the antioxidant.

[0114] When the tolerance of the antioxidant to the acid, i.e., sulfuric acid, decreases, a larger amount of the antioxidant is dissolved in the sulfuric acid solution, and its absorption intensity increases; when the tolerance of the antioxidant to the acid, i.e., sulfuric acid, increases, the absorption intensity of the sulfuric acid solution in which the antioxidant is dissolved decreases. Therefore, by observing the absorption intensity of the sulfuric acid solution in which the antioxidant is dissolved at a wavelength of 320 nm (corresponding to Ce included in the antioxidant), the absorption intensity of the sulfuric acid solution in which the antioxidant is dissolved decreases. 4+ The change in the absorption intensity of the ion at the characteristic value of the absorption wavelength in the UV-visible spectrum can detect the acid resistance of the antioxidant.

[0115] When measuring the absorption intensity, the sulfuric acid solution in which the antioxidant was dissolved was diluted with deionized water at a volume ratio of 1:0.75. The measurement results are shown in Fig. 9 middle.

[0116] like Fig. 9 As shown, it can be understood that when the secondary annealing is performed, the UV-visible absorption intensity of the antioxidant is equal to or slightly greater than the UV-visible absorption intensity of the antioxidant that is not subjected to the secondary annealing.

[0117] Therefore, it can be understood that the antioxidant obtained by the primary annealing and the secondary annealing has excellent antioxidant ability and acid resistance.

[0118] According to various exemplary embodiments of the present invention, an antioxidant may exhibit excellent antioxidant ability and acid resistance in an acid environment of a polymer electrolyte membrane fuel cell for a vehicle.

[0119] The invention has been described in detail with reference to exemplary embodiments thereof. However, it will be appreciated by those skilled in the art that changes may be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined in the claims and their equivalents.

Claims

1. A method for manufacturing an antioxidant for a fuel cell, the method comprising the steps of: Preparing samarium-doped cerium oxide; Performing a first annealing on the compound; and Performing a second annealing on the resulting product obtained by the first annealing to obtain an antioxidant, wherein the first annealing is performed at a temperature of 100°C to 1000°C, and the second annealing is performed at a temperature equal to or lower than the first annealing temperature.

2. The method according to claim 1, wherein the compound is represented by Chemical Formula 1, [Chemical Formula 1] Sm x What 1-x A 2-δ , where 0 < x ≤ 0.5, and δ represents the value of oxygen vacancies that renders the compound shown in Chemical Formula 1 electrically neutral.

3. The method according to claim 1, wherein the first annealing and the second annealing are each performed for 10 minutes to 10 hours.

4. The method according to claim 1, wherein the first annealing is performed in an atmospheric atmosphere, and the second annealing is performed in a gas atmosphere including hydrogen.

5. The method according to claim 1, wherein the antioxidant obtained by the secondary annealing has a higher relative humidity at 553 cm-1 than the generated product obtained by the primary annealing. -1 and 600cm -1 The Raman peak intensity is greater.

6. A fuel cell, comprising: A membrane electrode assembly including an electrolyte membrane and a pair of electrodes formed on two surfaces of the electrolyte membrane; A gas diffusion layer; and A separator, wherein at least one of the electrolyte membrane, the electrodes, and the gas diffusion layer includes an antioxidant manufactured by the method according to claim 1.

7. The fuel cell according to claim 6, wherein the compound is represented by Chemical Formula 1, [Chemical Formula 1] Sm x What 1-x A 2-δ , where 0 < x ≤ 0.5, and δ represents the value of oxygen vacancies that renders the compound shown in Chemical Formula 1 electrically neutral.

8. The fuel cell according to claim 6, wherein the antioxidant has main diffraction peaks in the XRD spectrum at regions of 2θ = 28 ± 1.0°, 32 ± 1.0°, 47 ± 1.0°, and 56 ± 1.0°.

9. The fuel cell according to claim 6, wherein the antioxidant has a microcrystalline size of 5 nm to 50 nm.

10. The fuel cell according to claim 6, wherein the antioxidant has a 10 m 2 / g to 200m 2 / g BET specific surface area.

11. The fuel cell according to claim 6, wherein the electrolyte membrane includes 100 ppm to 100000 ppm of the antioxidant.

12. A vehicle, comprising the fuel cell according to claim 6.

Citation Information

Patent Citations

  • Electrode for polymer electrolyte membrane fuel cell and method for forming membrane-electrode assembly using the same

    CN102082275A

  • Redox tolerant anode compositions for fuel cells

    CN109314227A